2016
DOI: 10.1038/srep27849
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 7 affects the pathogenesis of non-alcoholic fatty liver disease

Abstract: Recently, a possible link between toll-like receptor 7 (TLR7) and liver disease was suggested, although it was limited to fibrosis. Based on this report, we investigated whether TLR7 has a pivotal role in non-alcoholic fatty liver disease (NAFLD). The TLR7 signaling pathway, which is activated by imiquimod (TLR7 ligand) naturally, induced autophagy and released insulin-like growth factor 1 (IGF-1) into medium from hepatocytes. Lipid accumulation induced by unsaturated fatty acid (UFA; arachidonic acid:oleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 50 publications
1
24
1
Order By: Relevance
“…However, the mechanisms that contribute to progression to acute AH remain unclear. In mouse hepatocytes, fat accumulation was associated with decreased TLR 7 expression (Kim et al., ); however, in our human liver biopsy studies, NASH did not show decreased TLR 7 mRNA expression. Our research indicates that both the TLR 7 receptor and let‐7 micro RNA s, endogenous ligands of TLR 7, are increased in patients with AH .…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…However, the mechanisms that contribute to progression to acute AH remain unclear. In mouse hepatocytes, fat accumulation was associated with decreased TLR 7 expression (Kim et al., ); however, in our human liver biopsy studies, NASH did not show decreased TLR 7 mRNA expression. Our research indicates that both the TLR 7 receptor and let‐7 micro RNA s, endogenous ligands of TLR 7, are increased in patients with AH .…”
Section: Discussioncontrasting
confidence: 74%
“…Previous studies have reported altered hepatocyte TLR7 expression in patients with liver disease (Firdaus et al., ; Leake, ; Lee et al., ; Lin et al., ), including end‐stage alcoholic cirrhosis (Starkel et al., ), and have found TLR7 responses in hepatocyte cell lines (e.g., HepG2, Huh‐7) (Lee et al., ; Sarkar et al., ). Interestingly, unsaturated fatty acids reduce TLR7 expression, increase insulin‐like growth factor 1 (IGF1), and increase oxidative stress in mouse hepatocytes and genetic ablation of TLR7 led to fatty liver, reactive free radicals, and IGF1 up‐regulation in TLR7 knockout mice, consistent with the involvement of TLR7 in hepatic fat accumulation (Kim et al., ). TLR7 responds to ssRNA, including viral ssRNA such as hepatitis C virus (HCV) (Negash et al., ), linking TLR7 to chronic viral hepatitis‐associated cirrhosis HCC.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…NAFLD patients are at increased risk of liver-related diseases and have an elevated risk of cardiovascular disease and mortality, and NAFLD is rapidly becoming the leading indication for liver transplantation [2]. The mechanism underlying NAFLD pathophysiology remains elusive; however, a "two-hit" hypothesis has been suggested as a possible mechanism of pathological change in chronic liver disease [3]. Simple hepatic steatosis caused by lipid accumulation represents the "first hit" in the pathological process [4].…”
Section: Introductionmentioning
confidence: 99%
“…Two animal studies in cholestatic and nonalcoholic fatty liver disease seem in favor of a protective effect of TLR7 against disease progression and fibrosis . Expression of TLRs, including TLR7, was also elevated in a chronic ethanol‐feeding model.…”
Section: Discussionmentioning
confidence: 98%